موازنات وحدات الإدارة المحلية في سورية - خير علاء; إدلبي منى (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Local administration units in Syria have its own legal personality with financial and administration independence. The purpose of that is to give these units the ability to plan, execute and put development plans especially for the local society and executing them, in order to support its local developmental role next to its service role to achieve the principle of democracy which makes people the source of authorities. Those Units should have a financial position allows it to achieve this role through supporting its income and organizing its Receipts and expenditures in its own budget separated from general state budget and related to it according to the rules and regulations which control this relation. consequently, the law given the governorate the authority to prepare its own independent budgets to execute local projects, beside its budgets for municipal sector, which include the budgets of its administrative units, and have service character more than developmental character. تتمتع وحدات الإدارة المحلية في سورية بالشخصية الاعتبارية والاستقلال المالي والإداري، والهدف من ذلك هو جعل تلك الوحدات قادرة ًعلى التخطيط، والتنفيذ، ووضع الخطط التنموية الخاصة بالمجتمع المحلي، وتنفيذ المشاريع الخاصة بها؛ تعزيزاً لدورها التنموي المحلي، إلى جانب دورها الخدمي؛ تطبيقاً لمبدأ الديمقراطية الذي يجعل الشعب مصدر كل سلطة. ولتمكين تلك الوحدات من القيام بهذا الدور، كان لابد من تمتعها بمركزٍ مالي يخولها النهوض بالمهام الملقاة على عاتقها، من خلال تعزيز إيراداتها المالية، وتنظيم نفقاتها وإيراداتها في إطار موازنات خاصة بها منفصلة عن الموازنة العامة للدولة، ومرتبطة بها وفقاً للقوانين الناظمة لتلك العلاقة؛ فتم منح المحافظات صلاحية إعداد موازنات مستقلة لتنفيذ مشاريع محلية، إلى جانب موازناتها لشؤون القطاع البلدي التي تشمل موازنات الوحدات الإدارية التابعة لها، والتي تحمل طابعاً خدمياً أكثر منه تنموياً.